Management of syndactyly: a clinical study - Nangineedi, Nagaprasad; Harish, Gangavaram Praveen; Rafi, Mohammed (International Surgery Journal, 2019)
Background: Syndactyly is a congenital anomaly, basic principles of surgical release of syndactyly have been well established, each patient requires a thorough assessment of the soft-tissue and bony components in the syndactylized region. Reconstruction must be planned carefully when more than two digits are involved or when the syndactyly is a component of a systemic congenital syndrome. The aim of the treatment strategies for syndactyly is to separate the fused digits, create a functional hand, and produce an aesthetically acceptable web. Methods: The prospective clinical study is conducted in the Department of Plastic & Reconstructive surgery, between October 2016 to October 2018. Twenty six patients with congenital syndactyly and post burn syndactyly of fingers were included in this study. Results: There were no intra operative complications and no cases had any neurovascular compromise. Integrity of Dorsal and volar flaps, quality of scars, aesthetical aspects of fingers are reasonably good in almost all the cases that are operated in this study. Overall 97% of patients treated achieved good function and superior results following single surgery. Conclusions: Primary syndactyly is more common than secondary syndactyly. In this study the primary goal is separation of fused digits/toes and covering the web space with dorsal flap, and covering the separated digits/ toes with a graft and create a functional hand and produce an aesthetically web with fewest complications and fewest surgical corrections.